Geographical distribution and genetic diversity of Plasmodium vivax reticulocyte binding protein 1a correlates with patient antigenicity - Park, J-H; Kim, M-H; Sutanto, E; Na, S-W; Kim, M-J; Yeom, JS; Nyunt, MH; Abbas Elfaki, MM; Abdel Hamid, MM; Cha, SH; Alemu, SG; Sriprawat, K; et al. (Public Library of Science, 2022)
Plasmodium vivax is the most widespread cause of human malaria. Recent reports of drug resistant vivax malaria and the challenge of eradicating the dormant liver forms increase the importance of vaccine development against this relapsing disease. P. vivax reticulocyte binding protein 1a (PvRBP1a) is a potential vaccine candidate, which is involved in red cell tropism, a crucial step in the merozoite invasion of host reticulocytes. As part of the initial evaluation of the PvRBP1a vaccine candidate, we investigated its genetic diversity and antigenicity using geographically diverse clinical isolates. We analysed pvrbp1a genetic polymorphisms using 202 vivax clinical isolates from six countries. Pvrbp1a was separated into six regions based on specific domain features, sequence conserved/polymorphic regions, and the reticulocyte binding like (RBL) domains. In the fragmented gene sequence analysis, PvRBP1a region II (RII) and RIII (head and tail structure homolog, 152–625 aa.) showed extensive polymorphism caused by random point mutations. The haplotype network of these polymorphic regions was classified into three clusters that converged to independent populations. Antigenicity screening was performed using recombinant proteins PvRBP1a-N (157–560 aa.) and PvRBP1a-C (606–962 aa.), which contained head and tail structure region and sequence conserved region, respectively. Sensitivity against PvRBP1a-N (46.7%) was higher than PvRBP1a-C (17.8%). PvRBP1a-N was reported as a reticulocyte binding domain and this study identified a linear epitope with moderate antigenicity, thus an attractive domain for merozoite invasion-blocking vaccine development. However, our study highlights that a global PvRBP1a-based vaccine design needs to overcome several difficulties due to three distinct genotypes and low antigenicity levels.